Methylophiopogonanone A Protects against Cerebral Ischemia/Reperfusion Injury and Attenuates Blood-Brain Barrier Disruption In Vitro - Lin, Mingbao; Sun, Wei; Gong, Wan; Zhou, Zhiyu; Ding, Yasi; Hou, Qi (PLOS ONE, 2015)
Methylophiopogonanone A (MO-A), an active homoisoflavonoid of the Chinese herb Ophiopogon japonicus which has been shown to have protective effects on cerebral ischemia/reperfusion (I/R) injury, has been demonstrated to have anti-inflammatory and anti-oxidative properties. However, little is known about its role in cerebral I/R injury. Therefore, in this study, by using a middle cerebral artery occlusion (MCAO) and reperfusion rat model, the effect of MO-A on cerebral I/R injury was examined. The results showed that MO-A treatment reduced infarct volume and brain edema, improved neurological deficit scores, reversed animal body weight decreases, and increased animal survival time in the stroke groups. Western blotting showed that MO-A suppressed MMP-9, but restored the expression of claudin-3 and claudin-5. Furthermore, transmission electron microscopy were monitored to determine the blood–brain barrier (BBB) alterations in vitro. The results showed that MO-A markedly attenuated BBB damage in vitro. Additionally, MO-A inhibited ROS production in ECs and MMP-9 release in differentiated THP-1 cells in vitro, and suppressed ICAM-1 and VCAM-1 expression in ECs and leukocyte/EC adhesion. In conclusion, our data indicate that MO-A has therapeutic potential against cerebral I/R injury through its ability to attenuate BBB disruption by regulating the expression of MMP-9 and tight junction proteins.